2015
DOI: 10.1007/s00726-014-1897-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with DISC1 protein in an animal model of ADHD influences behavior and excitatory amino acids in prefrontal cortex and striatum

Abstract: The Disrupted-in-schizophrenia 1 (DISC1) gene is involved in vulnerability to neuropsychiatric disorders. Naples high-excitability (NHE) rat model neuropsychiatric problems characterized by an unbalanced mesocortical dopamine system. Here, we assessed behavioral and neurochemical effects of immunization against multimeric rat DISC1 protein in adult NHE rats, an animal model of attention-deficit hyperactivity disorder and their Random-Bred (NRB) controls. Males of both lines received subcutaneous injections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Consistent with these findings, a questionnaire-and performance-based assessment of Romanian children found significant associations of ADHD-like behavior with BLL but not with other toxic metals, notably Hg and Al [83]. Interestingly, animal studies have also provided evidence for similar hyperactivity and attention deficits in rodents exposed to Pb [84][85][86][87].…”
Section: Neurobehavioral Effects Of Early-life Pb Exposurementioning
confidence: 58%
“…Consistent with these findings, a questionnaire-and performance-based assessment of Romanian children found significant associations of ADHD-like behavior with BLL but not with other toxic metals, notably Hg and Al [83]. Interestingly, animal studies have also provided evidence for similar hyperactivity and attention deficits in rodents exposed to Pb [84][85][86][87].…”
Section: Neurobehavioral Effects Of Early-life Pb Exposurementioning
confidence: 58%
“…spontaneously hypertensive rats [56] or Naples High-excitability rats (Ruocco et al, 2015) [57], SNAP-25-deficient mutant coloboma mice (Baca et al, 2013) [58] or Cadherin-13, risk gene for ADHD (Rivero et al, 2015) [59]; further, Nr3c1-Bhlhb2, transcription factor silencing, axis dysregulation was involved in the development of ADHD through a disruption of prefrontal cortex functioning (Wu et al, 2016) [60]. In a pair-matching case-control study of ADHD children, it was found that Aberrant DNA methylation and histone acetylation was established in ADHD by applying the combination of p300, MYST4 and HDAC1 to obtain an accuracy of 0.9338 (Xu et al, 2015) [61].…”
mentioning
confidence: 99%